Determinación de creatinina en trabajadores de la industria del calzado expuestos a pegamentos sintéticos en el distrito el porvenir – sector miguel grau.” - Corbera Alfaro, Jorge Luis (2008)
This study was made with the purpose of determining the concentration creatinine in workers in the footwear industry exposed to synthetic glues. Urine samples were collected from 50 workers in the El Porvenir district – zone Miguel Grau, being processed for the determination of this compound. The results were expressed as age, sex and time of work, found concentrations downsampled than 0.9 g / 24hrs creatinine in 20% of the analyzed samples. Normal concentrations in 36 % and increased in 44 %. The creatinine concentrations that the normal values are between 0.9 to 1.5 g/24hrs according to the WHO. Keywords: Toluene, creatinine, glues, footwear industry.